Elements of Non-Linear Hamiltonian Dynamics - Egydio de Carvalho, R.; IOP (Iop Publishing Ltd, 2013)
In this paper we present a set of generic results on Hamiltonian non-linear dynamics. We show the necessary conditions for a Hamiltonian system to present a non-twist scenario and from that we introduce the isochronous resonances. The generality of these resonances is shown from the Hamiltonian given by the Birkhof-Gustavson normal form, which can be considered a toy model, and from an optic system governed by the non-linear map of the annular billiard. We also define a special kind of transport barrier called robust torus. The meanders and shearless curves are also presented and we show the most robust shearless barrier associated with the rotation numbers.
Keywords: isochronous resonances; robust torus; meandering tori; shearless curves